Application of metagenomic next-generation sequencing in the etiological diagnosis of refractory pneumonia in children - Wang, Ya-nan; Wu, Yu-ting; Cao, Ling; Niu, Wen-quan (Frontiers in Microbiology, 2024)
Objective: Metagenomic next-generation sequencing (mNGS) was used to analyse the aetiological distribution of refractory pneumonia in children. Methods: A total of 60 children with refractory pneumonia treated at the Department of Respiratory Medicine, Children's Hospital Affiliated with the Capital Institute of Paediatrics, from September 2019 to December 2021 were enrolled in this study. Clinical data and lower respiratory tract specimens were collectedand and mNGS detection methods were used to determine the distribution of pathogens and to compare the positive rate and diagnostic efficiency of mNGS and traditional pathogen detection for different types of pathogens. Results: Among the 60 children with refractory pneumonia, 43 specimens were positive by mNGS, and 67 strains of pathogens were detected, including 20.90% of which were Mycoplasma pneumoniae, 11.94% were Streptococcus pneumoniae, 7.46% were cytomegalovirus, and 5.97% were Candida albicans. Thirty-nine strains of Mycoplasma pneumoniae (41.03%), Streptococcus pneumoniae (10.26%), Candida albicans (7.69%) and Aspergillus (5.13%) were detected by traditional methods. The positive rate of mNGS detection was 90.48%, and the positive rate of the traditional method was 61.90% (P=0.050), especially for G+ bacteria. The positive rate of mNGS was greater than that of traditional methods (P < 0.05), but they had no significant difference in detecting G- bacteria, viruses, fungi, or Mycoplasma/Chlamydia. Among the 60 patients, 21 had mixed infections, 25 had single infections, and the other 14 had unknown pathogens. Mycoplasma pneumoniae was most common in both mixed infections and single infections. The sensitivity, specificity, positive predictive value and negative predictive value of mNGS were 95.45%, 37.50%, 80.77% and 75.00%, respectively. The traditional methods' sensitivity, specificity, positive predictive value and negative predictive value were 72.72%, 62.50%, 84.21% and 45.45%, respectively. The clinical compliance of mNGS was 80.00%, and that of the traditional method was 70.00%. The sensitivity and negative predictive value of mNGS were high, and the difference in the sensitivity for detecting G+ bacteria was statistically significant (p < 0.05). The differences in G- bacteria, fungi and Mycoplasma/Chlamydia were not statistically significant (p > 0.05). Conclusion: mNGS has higher overall efficacy than traditional methods for the aetiological diagnosis of refractory pneumonia in children.